Localizing Heritage Commission’s Website in Saudi Arabia (Arabic –English) Between Domestication and Foreignization - Almanjumi, Atheer (International Journal of Linguistics and Translation Studies, 2025)
The current paper discusses the localization of the Heritage Commission’s website in Saudi Arabia concerning Venuti’s foreignization and domestication strategies. The study examines the translation strategies involved in localizing the Heritage Commission’s website in Saudi Arabia from Arabic to English. In addition, to investigate the most common strategy used in localizing the website. Therefore, the comparative qualitative and quantitative methods will analyze the data collected. Observations while studying indicate that the procedure for literal translation, transliteration, and descriptive equivalence is closely related to foreignization. It is noted that transposition, omission, addition and adaptation will be included in domesticating procedures. The study revealed that the website can be localized by domestication or foreignization depending upon the factors affecting the text, such as culture. Foreignization is the most frequently used method of localizing the Heritage Commission website in Saudi Arabia.